Severe neonatal hypercalcemia secondary to Aluminium toxicity - Shrivastava, Bijal; Dipak, Niraj Kumar; Karajagi, Amit; Doshi, Rachit (International Journal of Contemporary Pediatrics, 2017)
Aluminum, the most abundant metal on the planet, though inert can lead to toxicity when repeatedly exposed. Infants mainly get exposed to aluminum via formula milk whereas NICU babies are exposed to it through parenteral nutrition. Moreover, in pre-term babies with feed intolerance, when added with aluminum containing antacids develop abnormal accumulation of aluminum. Aluminum toxicity inadvertently leads to hypophosphatemia, metabolic bone diseases with occasional hypercalcemia as well as many other systemic involvements in the form of encephalopathy, dementia and microcytic anaemia. With stoppage of oral antacid, transition from parenteral nutrition to enteral feeds and supplementation of phosphate, causes gradual resolution of toxicity over a period of time.